Logika Maqāṣid Al-Syarī‘ah Sebagai Paradigma Kritik Dalam Rekonstruksi Hukum Islam - Jasmin, Suriah Pebriyani; HL, Rahmatiah; Sultan, Lomba (Institut Agama Islam Negeri (IAIN) Bone, 2025)
Rapid social change and the increasing complexity of modern legal issues have created serious challenges to the relevance and justice of Islamic law in the contemporary era. Many textual provisions of Islamic law often confront dynamic social realities, thereby necessitating a critical paradigm for interpreting and reconstructing the law so that it remains contextual and oriented toward the realization of public welfare (maṣlaḥah). In this context, this research becomes urgent as it explores the logic of maqāṣid al-syarī‘ah as a critical paradigm in the reconstruction of Islamic law. Maqāṣid al-syarī‘ah, which was originally understood as the normative objective of the Sharī‘ah aimed at protecting the five essential human needs (al-ḍarūriyyāt al-khamsah) religion, life, intellect, lineage, and property has undergone a significant expansion in both meaning and function. In contemporary development, maqāṣid is no longer confined merely to preserving welfare but has evolved into an epistemological and critical framework for assessing the relevance, justice, and benefit of Islamic law in responding to modern social dynamics. By employing a maqāṣid-based approach, Islamic law is no longer rigidly understood through textual formalism but becomes open to reinterpretation in accordance with the principles of justice, welfare, gender equality, and respect for human rights. This study employs a qualitative method using hermeneutical analysis of both classical and modern literature. The rapid social transformation and the emergence of modern legal problems such as child marriage, gender equality, bioethics, environmental issues, and social justice emphasize the urgent need for a new paradigm in understanding Islamic law to ensure its continued relevance and fairness. In this regard, the study situates the logic of maqāṣid al-syarī‘ah as a critical paradigm for reconstructing Islamic law. Originally serving to preserve the five essential human needs (al-ḍarūriyyāt al-khamsah), maqāṣid has now evolved into an epistemological framework capable of critically evaluating and dynamically interpreting Islamic law. Findings from various studies indicate that the application of maqāṣid to contemporary issues demonstrates its potential as a bridge between normative texts and social realities, thus establishing maqāṣid al-syarī‘ah as an essential instrument in developing an Islamic legal system that is adaptive, progressive, humanistic, and contextually grounded Perubahan sosial yang cepat dan kompleksitas persoalan hukum modern menimbulkan tantangan serius bagi relevansi dan keadilan hukum Islam di era kontemporer. Banyak ketentuan hukum Islam yang bersifat tekstual sering kali dihadapkan pada realitas sosial yang dinamis, sehingga menuntut adanya paradigma kritis dalam menafsirkan dan merekonstruksi hukum agar tetap kontekstual dan berorientasi pada kemaslahatan. Dalam konteks inilah, penelitian ini menjadi urgen karena membahas logika maqāṣid al-syarī‘ah sebagai paradigma kritik dalam rekonstruksi hukum Islam. Maqāṣid al-syarī‘ah yang semula dipahami sebagai tujuan normatif syariat untuk melindungi lima kebutuhan pokok manusia (al-ḍarūriyyāt al-khamsah) agama, jiwa, akal, keturunan, dan harta kini mengalami perluasan makna dan fungsi. Pada perkembangan kontemporer, maqāṣid tidak lagi diposisikan sekadar sebagai instrumen pemeliharaan kemaslahatan, melainkan juga sebagai kerangka epistemologis dan kritis untuk menilai relevansi, keadilan, serta kemanfaatan hukum Islam dalam menghadapi dinamika sosial modern. Dengan menggunakan pendekatan maqāṣid, hukum Islam tidak lagi dipahami secara kaku melalui formalisme tekstual, melainkan terbuka terhadap reinterpretasi sesuai prinsip keadilan, kemaslahatan, kesetaraan gender, dan penghormatan terhadap hak asasi manusia. Penelitian ini menggunakan metode kualitatif dengan analisis hermeneutik terhadap literatur klasik dan modern.Perubahan sosial dan munculnya problematika hukum modern seperti perkawinan anak, kesetaraan gender, bioetika, lingkungan hidup, dan keadilan sosial menegaskan urgensi paradigma baru dalam memahami hukum Islam agar tetap relevan dan berkeadilan. Dalam konteks ini, penelitian ini menempatkan logika maqāṣid al-syarī‘ah sebagai paradigma kritik dalam rekonstruksi hukum Islam. Maqāṣid yang semula berfungsi menjaga lima kebutuhan pokok manusia (al-ḍarūriyyāt al-khamsah) kini berkembang menjadi kerangka epistemologis yang mampu menilai dan menafsirkan hukum Islam secara lebih dinamis. Hasil berbagai kajian menunjukkan bahwa penerapan maqāṣid pada isu-isu kontemporer memperlihatkan potensinya sebagai jembatan antara teks normatif dan realitas sosial, sehingga menjadikan maqāṣid al-syarī‘ah instrumen penting dalam membangun hukum Islam yang adaptif, progresif, humanis, dan kontekstual.